Identification and characterization of a curly-leaf locus CL1 encoding an IAA2 protein in Brassica napus - Yingchao Tan; Lanyang Ren; Jia Wang; Shuyao Ran; Liusha Wu; Ziyi Cheng; Cunmin Qu; Jiana Li; Liezhao Liu (Crop Journal, 2023)
The leaf is the main organ for rapeseed photosynthesis, and its morphology influences photosynthetic efficiency and supports increased planting density and yield. However, the molecular regulatory mechanism of leaf morphology in Brassica napus is poorly understood, restricting progress in breeding for the trait. We describe a novel dominant mutation, curly leaf 1 (cl1), which confers uneven dorsal–ventral axis development, irregular cellular structure and influenced gravitropic response in the seedling stage. The CL1 locus was mapped to a 1.573-Mb interval on chromosome A05 using simple sequence repeat (SSR) markers, and co-segregated with the phenotype of plants in the curly F2 population. A substitution (P62S) was identified in the highly conserved degron motif (GWSPV) of the IAA2 protein in the cl1 mutant, and the P62S substitution impaired the interaction between IAA2 and TIR1 in the presence of auxin, influencing auxin signaling. The P62S substitution-induced curly leaf phenotype was verified by ectopic expression of BnaA05.iaa2 in Arabidopsis and B. napus. Our findings explain the function of IAA2 in rapeseed, providing a foundation for future investigation of auxin signaling and the mechanisms underlying leaf development in B. napus.